The influence of market orientation, entrepreneurial orientation and social media marketing on MSME marketing performance case study: Ismea Member - Ahmad Juwaini,; Indupurnahayu,; Popy Novita Pasaribu,; Effi Indriana, (Technium Business and Management, 2022)
This study aims to analyze the impact of market orientation, entrepreneurial orientation, and social media marketing on the marketing performance of MSMEs that are members of ISMEA. This type of research is quantitative research. The study population consisted of 200 ISMEA members. the number of samples taken were as many as 67 respondents. The research instrument used was a questionnaire. The results of the analysis using multiple regression techniques. The results of the F test showed a significance value of 0.000 <0.05, and a calculated F value of 52.374 > from F table 3.134. This shows the alternative hypothesis is accepted. That is, simultaneously, market orientation, entrepreneurial orientation, and social media marketing have an influence on marketing performance. The results of the (partial) t test show that the significance value of market orientation is 0.151 < than 0.05, and the calculated t value is 1.855 > from t table 1.67. This shows the alternative hypothesis is accepted. That is, market orientation has a significant effect on marketing performance, and the value of entrepreneurial orientation is 0.0391 > 0.05. Then the alternative hypothesis is accepted. This shows that entrepreneurial orientation has a significant influence on marketing performance. The results of the t test (partial) show that the effect of social media marketing on marketing performance is a t count of 1.972 > t table of 1.67. Therefore, the social media marketing alternative hypothesis is accepted. That is, there is an influence between social media marketing and marketing performance.